EVALUASI PENERAPAN PROGRAM IPAL (INSTALASI PENGOLAHAN AIR LIMBAH) KOMUNAL DI KOTA BANDA ACEH - Aulia Rohendi; Syamsud Dhuha; Cut Syarmila Sugesti; Adian Aristia Anas; Yeggi Darnas (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2021)
One solution for domestic waste treatment is the operation of a communal IPAL (WWTP, Wastewater Treatment Plant). This is in accordance with SDG's (Sustainable Development Goals), national and regional policies related to sustainable sanitation management. In Banda Aceh, the Sanimas (Community sanitation) program has been and is being implemented in 40 gampongs (villages) which are classified as slum areas. This study aims to determine the results of the effluent processing of the IPAL system (pH, BOD, COD, TSS, ammonia, Total Coliform, Oil/Fat parameters) to see whether the IPAL system that has been built is operating properly. There were five IPALs studied, namely in Gampong Peunayong (Dusun Cendrawasih), Gampong Tibang (Dusun Tgk. Meurah, Dusun Tgk Meulinje, Dusun Tengku Meulagu), and Gampong Panteriek (Dusun Jeumpa). The results of the effluent wastewater test showed that in all WWTPs, the BOD and COD parameters still exceeded the wastewater quality standards, and in one WWTP, the total Coliform parameter was >1,000/100 ml (quality standard >3,000/100 ml).